Scientific analysis of human capital development as the factor of territory competitiveness increase - Arnaut, Marina N.; Nedoluzhko, Olga V. (Nexo Revista Científica, 2022)
The relevance is in a specific problem - the contradiction between a particular territory competitiveness increase (for example, the gross regional product, budget financing) and the population interest in implementing their qualitative and quantitative characteristics (human capital) on it. The article proposes the author's approach of proving the position that the specificity of human capital development can be both a constraining and an activating factor for a territory competitiveness increase. It has been determined that the influence nature (positive or negative) is set by a combination of factors that are the main elements of mutual influence mechanisms of human capital qualitative and quantitative components and the rates of socio-economic development of a territory, which characterize its level of competitiveness. The results obtained can be used by researchers who deal with the problems of human capital theory, its development, and the relationship with the territory competitiveness indicators. The study's practical significance is the possibility of its result application: by state authorities and local self-government during the development and adjustment of documents for territory development strategic planning; the scientific community during the study of human capital and the level of territory competitiveness mutual influence.